Ensuring food safety in the European Union - Silano, V.; Silano, Marco (Boca Raton, FL ; Milton Park, Abingdon, Oxon : CRC Press, Taylor and Francis, 2021)
It's not easy to navigate through EU food laws, so this book provides a clear analysis of the relevant EU regulations, making it beneficial to food safety organizations and food industry professionals. Ensuring Food Safety in the European Union provides an overall detailed analysis of the many and complex initiatives implemented by the European Union Institutions since the European Commission adopted on 12 January 2000 the "White Paper on Food Safety" with the objective of defining the policies to improve the level of health protection for the consumers of Europe's food. Achieving the highest standards of food safety in Europe has been a key policy priority for the European Institutions during the past 20 years through the implementation between 2000 and 2019 of many initiatives anticipated in the mentioned White Paper concerning: (i) The establishment of the European Food Safety Authority; (ii) the adoption of new food safety legislations in many domains; and (iii) the adoption of consumer's mandatory and voluntary information regulations. Features Offers a clear and evolutive view of all relevant procedures and objectives to ensure food safety in European context Up to date presentation of EU relevant regulation and EFSA roles and activities Discusses the basic reasoning underlying the development and objectives of the current approach to food laws The book offers a review of all the available tools and their practical usefulness on food safety at European level and their possible integration. The interest of the European Institutions for food safety policies continues to be very high as shown by the adoption in September 2019 of the EU regulation 1381 to further reinforce and potentiate, among others, EFSA risk assessment. The main target of the book is the food business operators of large and medium enterprises and their consultants. Other interested parties are the authorities competent at national and regional and local level and university teaching professionals in charge of food safety and related courses.
5.2.13 Readability Criteria -- 5.2.14 Mandatory Nutrition Information -- 5.2.15 Additional Forms of Expression and Presentation -- 5.3 Voluntary Consumer's Information -- 5.3.1 Nutrition Claims -- 5.3.2 Health Claims -- 5.3.2.1 General Function Health Claims Already in Use (Article 13.1) -- 5.3.2.2 General Function Health Claims Based on New Data Subject to Protection (Article 13.5) -- 5.3.2.3 Health Claims Ex Article 14A (Reduction of Disease Risk Claims) and 14B (Children Health and Development Claims) -- 5.3.3 Nutritional Profiles
OCLC-licensed vendor bibliographic record.
Keywords: Food law and legislation -- European Union countries; Food -- European Union countries -- Safety measures; Food industry and trade -- European Union countries; TECHNOLOGY / Food Science